The gathering : [large type] a novel - Tudor, C. J. (Random House Large Print, 2024)
"A detective investigating a grisly crime in rural Alaska finds herself caught up in the dark secrets and superstitions of a small town in this riveting novel from the acclaimed author of The Chalk Man. Deadhart, Alaska. Population: 673. Living. In a small Alaskan town, a boy is found with his throat ripped out and all the blood drained from his body. The inhabitants of Deadhart haven't seen a killing like this in twenty-five years. But they know who's responsible: a member of the Colony, an ostracized community of vampyrs living in an old mine settlement deep in the woods. Detective Barbara Atkins, a specialist in vampyr killings, is called in to officially determine if this is a Colony killing - and authorize a cull. Old suspicions die hard in a town like Deadhart, but Barbara isn't so sure. Determined to find the truth, she enlists the help of a former Deadhart sheriff, Jenson Tucker, whose investigation into the previous murder almost cost him his life. Since then, Tucker has become a recluse. But he knows the Colony better than anyone. As the pair delve into the town's history, they uncover secrets darker than they could have imagined. And then another body is found. While the snow thickens and the nights grow longer, a killer stalks Deadhart, and two disparate communities circle one another for blood. Time is running out for Atkins and Tucker to find the truth: Are they hunting a bloodthirsty monster . . . or a twisted psychopath? And which is more dangerous?"--